Talents, Competencies and Techniques of Business Analysts: Towards a Unified Theory - Anna BOBKOWSKA (Communications of International Proceedings, 2025)
Business analysis has been an important factor of success of software projects and business analysts are listed among top jobs of the future. However, training of effective business analysts is challenging and requires individualized professional development programs. This paper extends the previous research on the balanced approach to training business analyst with use of techniques, underlying competencies development and talent-oriented approaches. It argues for the need of unified theory which can be considered as a conceptual framework for integrating the background approaches. It applies integrative studies which allow to capture a broader scope of phenomena. The following research methods are in use: interpretation with meta-knowledge which explains the context of discovery and the values of the background approaches, cross-border analysis which allows to focus on connections and overlapping between the background approaches, and searching for common ground with use of conscious and non-conscious cognitive processes similar to forming habits or semi-automatic human behaviors. The findings deliver many interesting explanations of the phenomena as well as suggestions for practical use of this approach. For example, use of explicit descriptions of strengths (in terms of patterns of thought, feeling and behavior) for competence development; use of business analysis techniques for competence development; need for entire spectrum of competencies of business analyst comparing to specific strengths; possible problems with following the experts; and perspective of thinking in terms of forming and re-forming effective cognitive processes for more comfort in business analysts’ training.
Keywords: business analyst techniques; unified theory; competencies of business analyst; talents in professional development.